The impact of gestational diabetes mellitus on maternal-fetal pregnancy outcomes and fetal growth: a multicenter longitudinal cohort study - Su, Mi; Wang, Yangyang; Yuan, Qinqin; Tang, Dongmei; Lu, Yu; Wu, Xixi; Xiong, Wen; Li, Yalan; Liu, Tianjiao; Zeng, Siyuan; Wei, Sumei (Frontiers in Pediatrics, 2025)
ObjectiveTo investigate the impact of gestational diabetes mellitus (GDM) on maternal and neonatal pregnancy outcomes and fetal growth patterns.MethodsA cohort of 418 pregnant women was analyzed, comprising 203 with normal glucose tolerance and 215 diagnosed with GDM. Key maternal factors, including age, pre-pregnancy body mass index (BMI), gestational weight gain, and gestational hypertension, were assessed for their association with infant growth and food allergy outcomes. At six months of corrected gestational age, weight-for-age z-scores (WAZ) and food allergy incidence were compared between the two groups. Binary logistic regression and linear regression analyses were performed to identify significant predictors of these outcomes.ResultsInfants born to mothers with GDM exhibited significantly higher WAZ scores (p = 0.026) and an increased neonatal susceptibility to food allergies (p = 0.043) compared to those born to mothers with normal glucose tolerance. Maternal factors such as advanced age, higher pre-pregnancy BMI, gestational hypertension, and twin pregnancy were identified as key risk factors for GDM. Additionally, preterm birth, birth weight, and parental history of allergies were independently associated with the development of food allergies in infants.ConclusionGDM exerts a notable influence on infant growth trajectories and elevates the risk of food allergies. Effective glycemic management during pregnancy, early monitoring of infant development, and targeted interventions addressing risk factors such as preterm birth and parental allergy history are critical for mitigating long-term health risks in children exposed to GDM in utero. Further research is warranted to explore the underlying mechanisms and potential preventive strategies for this at-risk population.